Study of nitrogen limitation and seed nitrogen sources for historical and modern genotypes in soybean - Ortez, Osler Antonio Amador (Kansas State University, 2018)
Soybean [Glycine max (L.) Merr.] yields have continuously increased over time. Seed yields are determined by the genotype, environment, and management practices (G × E × M) interaction. Closing yield gaps require a continuous improvement in the use of the available resources, which must be attained via implementation of better management decisions. Linear relationships between seed yield and nitrogen (N) demand are reported in the scientific literature. Main sources of N to the plant are the biological N fixation (BNF) and the soil mineralization processes. On overall, only 50-60% of soybean N demand is met by the BNF process. An unanswered scientific knowledge is still related to the ability of the BNF to satisfy soybean N demand at varying yield levels. Seed N demand not met by N fixation plus soil mineral N, is then fulfilled by the remobilization of N from vegetative organs during the seed filling period. An early remobilization process reduces the photosynthetic activity (leaves) and can limit seed yield. The objectives of this project were to: i) study yield improvements and contribution of N via utilization of contrasting N conditions under historical and modern soybean genotypes, and ii) quantify main seed N sources during the seed filling period. For objective one, four field experiments were conducted during the 2016 and 2017 growing seasons in Kansas, United States (US) and Santa Fe Province, Argentina (ARG). Those experiments investigated twenty-one historical and modern soybean genotypes with release decades from 1980s to 2010s. As for objective two, three field experiments were conducted during the 2015 and 2016 growing seasons in Kansas, US, studying three soybean genotypes: non-roundup ready (RR), released in 1997; RR-1, released in 2009; and RR-2, released in 2014. Across all studies, seeds were inoculated and tested under three N management strategies: i) control without N application (Zero-N); ii) 56 kg N ha⁻¹ applied at reproductive growth stages (Late-N); and iii) 670 kg ha⁻¹ equally split at three timings (Full-N). As for yield improvements and N limitation, soybean yield improvements from the 1980s to 2010s were documented, representing 29% increases in the US and 21% in ARG. Regarding N management, the Full-N fertilization produced a 12% increase in seed yields in the US and 4% in ARG. As for main seed N sources in objective two, remobilization accounted for 59% of seed N demand, and was negatively related to new N uptake occurring during the seed filling period. Seed N demand for greater yields was dependent on both, N remobilization and new N uptake, while for lower yields, seed N demand was mainly supported by the N remobilization process. These results suggest that: a) high seed yields are somehow limited by the availability of N to express their potential, although the question about N application still remains to be fully investigated, as related to the timing and the environment by plant interactions that could promote a N limitation in soybeans; b) remobilization accounts for majority (59%) of N sourced to the seed, and c) high yielding soybean (modern genotypes) rely on diverse N sources: the N remobilization process plus new uptake of N.
Keywords: Nitrogen fertilizer; Nitrogen uptake; Nitrogen remobilization; Seed yield improvement; Seed nitrogen sources; Historical and modern genotypes